THE EFFECT OF USING CALCIUM SOAP IN THE REDUCTION OF ABDOMENAL FAT IN BALI DUCKS (Anas sp) - N.W., Purnami; Candrawati, D. P. M. A.; Puspani, E. (Jurnal Peternakan Tropika; Vol 10 No 3 (2022): Vol. 10 No. 3 Tahun 2022; September - December, 2022)
The study aims to find out the effect of calcium soap supplementation in rations on the pad fat, mesenterium fat, ventricular fat and abdominal fat of balinese ducks. The design research used was a complete randomized design (RAL) with 4 treatments and 6 replications. Each trial cage will filled with four two week old Bali ducks with homogeneous weight. The four treatments were rations without calcium soap as a control (A) rations with 1% calcium soap (B), rations with 2 % calcium soap (C) and rations with 3 % calcium soap (D). the Variables observed in this study were pad fat, mesenterium fat, ventricular fat and abdomenal fat. The results of the study showed that adminstering of calcium soap weighting ratio of the duck cut given rations without calcium soap (A) as a control was 696.67g/tail. Duck pad fat receiving real B, C and D treatment (P<0.05) was lower compared to treatment (A), while mesenterium and ventriculus fat receiving real B, C and D treatment were lower (P >0.05) compared to treatment A, Duck abdomen fat receiving real B, C and D treatment (P<0.05) was lower compared to treatment (A). Calcium soap administration 1% in the ration got the best results in reducing abdominal fat, and Calcium soap administration to 3% can reduce fat bearing bali ducks, while the mesentery and ventriculus fat was the same as the control. Keywords: bali duck, abdominal fat, calcium soap, supplementation